TWEAK/Fn14 disrupts Th17/Treg balance and aggravates conjunctivitis by inhibiting the Nrf2/HO-1 pathway in allergic conjunctivitis mice - Yang Yang; Yuezhi Zhang; Jingfan Fu; Xiaolong Yin (BMC, 2024)
Abstract Background Allergic conjunctivitis (AC) affects people's daily life and work, especially the health of children. Although there are few relevant studies, Th17/Treg imbalance plays an important role in AC development. The aim of this study was to elucidate the effect of TWEAK/Fn14 on AC and Th17/Treg balance. Methods Ovalbumin induced AC mouse model was utilized to observe the mechanism of TWEAK/Fn14 in vivo. Conjunctivitis was evaluated by hematoxylin-eosin staining, toluidine blue staining and AC clinical score. Flow cytometry was used to measure Th17 and Treg cell ratios. The level of Th17/Treg balance related factors and Nrf2/HO-1 signal was detected by ELISA, WB, qRT-PCR and immunohistochemistry. Results In the AC state, disruption of Th17/Treg cell balance, increased TWEAK/Fn14 signaling level and conjunctival inflammation were observed. After TWEAK knockdown, Th17 cell differentiation was inhibited, Treg cell differentiation was promoted, and AC symptoms were alleviated in AC mice. Moreover, TWEAK knockdown caused an enhancement of the Nrf2/HO-1 signaling pathway in the AC models. Treatment with Nrf2 inhibitor reversed these changes induced by TWEAK knockdown. Therefore, TWEAK/Fn14 regulated the Nrf2/HO-1 pathway to affect Th17/Treg cell balance and conjunctivitis in AC mouse models. Conclusion In summary, TWEAK/Fn14 caused Th17/Treg imbalance by inhibiting Nrf2/HO-1 pathway, which might be one potential mechanism of the exacerbation of AC.